The Effect of Product Diversification on Purchase Decisions - LU'LU UL MAKNUNAH; Rania Eka Hariyanti Hariyanti (JARES (Journal of Academic Research and Sciences), 2022)
Amanah Souvenir Center Blitar City is a shop that provides processed snack products in the form of snacks including opak gambir, mongso honey, geti etc. This research aims to determine whether product diversification has an influence on consumer purchasing decisions at the Amanah Souvenir Center in Blitar City. In this paper, a survey research method is used with a quantitative research approach and data management software, namely Statistical Product and Service Solution (SPSS) version 16.0. The data was collected by distributing questionnaires or questionnaires to the respondents and the hypothesis analysis technique was carried out using the partial test method or t-test to 60 respondents. Based on a series of analysis and testing shows that for testing with t-test obtained a value of 0.009. In the t-test obtained a value of less than 0.05it can be interpreted that there is a positive and significant influence between product diversification on consumer purchasing decisions at the Amanah Souvenir Center Store in Blitar City.